2012
DOI: 10.1029/2012gl051977
|View full text |Cite
|
Sign up to set email alerts
|

The Indian summer monsoon during peaks in the 11 year sunspot cycle

Abstract: [1] An analysis of sea-level pressure anomalies at 14 sunspot peaks in the 11 year solar cycle in the Indian region in summer shows that the mean sea level pressure anomalies consist of relatively high pressure over land surrounded by low pressure anomalies over the sea. This signal is robust enough to appear when the data are divided into two segments. The accompanying mean rainfall anomalies, with anomalies as high as 20% above normal, have maxima on the coasts and over water and are an enhancement of the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…Nevertheless, if these boundaries move significantly with the solar cycle, their behavioral differences could reveal the solar cycle imprints. Many studies present evidence of a poleward shift or expansion in the high solar activity conditions of the Indian monsoon (Kodera 2004;van Loon and Meehl 2012), the Hadley cell, the subtropical jet, the Ferrel cell (Haigh 2003;Gleisner and Thejll 2003;Haigh et al 2005;Br€ onnimann et al 2007), and so on, and an equatorward shift in the low solar activity conditions of North Atlantic storm tracks (Martin-Puertas et al 2012). The differences in the location of the mei-yu rainband under different solar conditions presented in this paper are consistent with the oscillation of the northern boundary of the EASM related to the solar cycle as reported by Zhao et al (2012) and Wang and Zhao (2012).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Nevertheless, if these boundaries move significantly with the solar cycle, their behavioral differences could reveal the solar cycle imprints. Many studies present evidence of a poleward shift or expansion in the high solar activity conditions of the Indian monsoon (Kodera 2004;van Loon and Meehl 2012), the Hadley cell, the subtropical jet, the Ferrel cell (Haigh 2003;Gleisner and Thejll 2003;Haigh et al 2005;Br€ onnimann et al 2007), and so on, and an equatorward shift in the low solar activity conditions of North Atlantic storm tracks (Martin-Puertas et al 2012). The differences in the location of the mei-yu rainband under different solar conditions presented in this paper are consistent with the oscillation of the northern boundary of the EASM related to the solar cycle as reported by Zhao et al (2012) and Wang and Zhao (2012).…”
Section: Discussionmentioning
confidence: 97%
“…The possible preservation of solar cycle signals in precipitation has been reported from several monsoon regions, including South Asia, West Africa, and North America (e.g., Kodera 2004;van Loon et al 2004;Kodera and Shibata 2006;Narasimha and Bhattacharyya 2010;van Loon and Meehl 2012). This resembles the relationship between the solar cycle and other climate phenomena; however, the apparent correlation between the solar cycle and monsoon precipitation may differ over time and from region to region, even to the extent of adjacent regions having correlations with the opposite sign (e.g., Thresher 2002;Meehl et al 2009).…”
Section: Introductionmentioning
confidence: 98%
“…Numerous model studies have suggested that the spectrum solar irradiance interacting with ozone can strongly affect stratospheric temperature and circulation, which then propagate downward to alter tropospheric general circulation (Haigh 1996;Matthes et al 2006). Statistical correlations between the 11-year solar activity and the decadal climate variability have been found in the observations (Currie 1993;Soon 2005;Van Loon and Meehl 2012). At the peak years of the 11-year solar cycle, the climatological precipitation maxima in the tropical Pacific were found to be strengthened, further modulating the Pacific climate system, i.e., Pacific Decadal Oscillation (PDO) and El Niño-Southern Oscillation (ENSO) (Van Loon et al 2007;Meehl et al 2008.…”
Section: Introductionmentioning
confidence: 99%
“…These components are not independent of each other, as for example the ASM itself is influenced by ENSO (e.g. Webster and Yang, 1992), the QBO , or the 11-year solar cycle (van Loon and Meehl, 2012). As shown by Kunze et al (2010), the strength of the ASM has some influence on the observed H 2 O maximum and O 3 minimum mixing ratios confined by the AMA, with increasing H 2 O and decreasing O 3 mixing ratios during strong ASM seasons.…”
Section: Introductionmentioning
confidence: 99%